High‐Performance Nonfullerene Polymer Solar Cells Based on a Wide‐Bandgap Polymer without Extra Treatment. Issue 1 (22nd October 2018) - Li, Guangda; Xu, Qingqing; Chang, Chunmei; Fan, Qunping; Zhu, Xiaoqian; Li, Wanbin; Guo, Xia; Zhang, Maojie; Wong, Wai‐Yeung
Abstract: Nonfullerene polymer solar cells (PSCs) are developed based on a fluorinated thienyl‐based wide‐bandgap (WBG) polymer PBBF as the electron donor and nonfullerene small molecule IDIC as the electron acceptor. PBBF exhibits a strong absorption in the range of 300–605 nm with a wide optical bandgap of 2.05 eV, which is complementary with that of IDIC. Meanwhile, it possesses a deeper highest occupied molecular orbital energy level of  −5.52 eV and a higher hole mobility of 7.3 × 10 −4  cm 2 V −1  s −1 compared to the nonfluorinated polymer PBDTT. The PSCs based on PBBF :IDIC without extra treatment show a power conversion efficiency (PCE) of 8.5% with a V oc of 0.95 V, a J sc of 15.3 mA cm −2, and an FF of 58.8%, which is much higher than that of the devices based on PBDTT:IDIC (a PCE of 5.3% with a V oc of 0.88 V, a J sc of 13.7 mA cm −2, and an FF of 43.9%). These results indicate that PBBF is a promising WBG polymer donor material for the photovoltaic applications in nonfullerene PSCs. Abstract : Nonfullerene polymer solar cells (PSCs) based on a new wide‐bandgap polymer PBBF and a narrow bandgap acceptor IDIC exhibit a power conversion efficiency (PCE) of 8.5% without extra treatment, which is much higher than that of the devices based on PBDTT:IDIC. The result indicates that PBBF is a promising wide‐bandgap polymer donor material for photovoltaic applications in nonfullerene PSCs.